The perceptions of teenagers, young adults and professionals in the participation of bone cancer clinical trials. (3rd March 2016) - Pearce, S.; Brownsdon, A.; Fern, L.; Gibson, F.; Whelan, J.; Lavender, V.
Abstract : The reasons why teenagers and young adults (TYA) with cancer do, or do not, participate in clinical trials is not wholly understood. We explored the perceptions and experiences of young people with bone cancer, and health professionals involved in their care, with regard to participation in two clinical trials. We conducted semi‐structured interviews using narrative inquiry with 21 young people aged 15–24 years and 18 health professionals. New understandings emerged about perceptions of, and factors that influence participation in, clinical trials. These include perceptions about the importance and design of the clinical trial, communicating with young people in an age‐specific manner, using language young people are comfortable with, support from family, peers and specialists in teenage and young adult cancer care. We conclude that addressing these factors may increase acceptability of clinical trials and the trial design for TYA with cancer and ultimately improve their participation. Qualitative research has an important role in making explicit the perceptions and practices that ensure trials are patient‐centred, appropriate and communicated effectively to TYA. Translating knowledge gained into routine practice, will go some way in ensuring that the disparities affecting this population are more fully understood.